(untitled) (Research, Society and Development, 2021)
The purpose of this essay is to reflect on the intersubjective and intrasubjective relations of inhabit, analyzing gender dichotomies, under the interdisciplinary approach, highlighting the contribution of Architecture - from a House Theory, associated with psychoanalytic theory -, as well as the Law and Social Work, through the discussion of public policies aimed at combating gender violence in the domestic sphere as the constitutional guarantees. The problem starts from two assumptions, the first is the Freudian metaphor that the House is the substitute for the maternal womb and, therefore, it is configured - more than a human shelter - a place of "protection". The second reports on gender inequality in access to security housing - adopting Freudian helplessness as a reference center - which is found, above all, from domestic violence against women. To this end, the essay adopts a theoretical and qualitative character, drawing on bibliographic and doctrinal sources.